Green-lipped (greenshell™) mussel (Perna canaliculus) extract supplementation in treatment of osteoarthritis: a systematic review - Maryam Abshirini; Jane Coad; Frances M. Wolber; Pamela von Hurst; Matthew R. Miller; Hong Sabrina Tian; Marlena C. Kruger (Inflammopharmacology, 2021)
Objectives Intervention studies using New Zealand green-lipped or greenshell™ mussel (GSM) ( Perna canaliculus ) extract in osteoarthritis (OA) patients have shown effective pain relief. This systematic review summarises the efficacy of GSM extracts in the treatment of OA. Methods A literature search of the three databases EMBASE, MEDLINE, and Scopus was performed to identify relevant articles published up to March 2020. Inclusion criteria were clinical trials published in English measuring the effect of supplementation of whole or a lipid extract from GSM on pain and mobility outcomes in OA patients. Results A total of nine clinical trials were included in systematic review, from which five studies were considered appropriate for inclusion in a forest plot. Pooled results showed that GSM extracts (lipid extract or whole powder) provide moderate and clinically significant treatment effects on a visual analogue scale (VAS) pain score (effect size: − 0.46; 95% CI − 0.82 to − 0.10; p = 0.01). The whole GSM extract improved gastrointestinal symptoms in OA patients taking anti-inflammatory medications. The GSM extract was considered to be generally well tolerated in most of the studies. Conclusion The overall analysis showed that GSM provided moderate and clinically meaningful treatment effects on OA pain. However, the current evidence is limited by the number and quality of studies, and further larger and high-quality studies are needed to confirm the effectiveness and to identify the optimal GSM format. Nevertheless, it is worth considering using GSM extracts especially for patients seeking alternative pain relief treatments with fewer side effects compared to conventional treatment.